Efficient Sn(II)-catalyzed one-pot synthesis of a 3-substituted azetidine-2,4-dione framework - Chavan, Santosh S.; Supekar, Mrudul V.; Burate, Pralhad A.; Rupanwar, Bapurao D.; Shelke, Anil M.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2017)
A novel Sn(II)-catalyzed tandem cyclization reaction of aromatic aldehydes with ethyl cyanoacetate has been achieved to afford a series of 3-substituted azetidine-2,4-diones in good to excellent yields. This protocol provides straightforward access to construct the azetidine core through sequential Knoevenagel condensation, hydration and the C-N cyclization reaction.

AgNO3-Catalysed intramolecular cyclization: access to functionalized cyclopentanones and spiro-cyclopentanones - Bhoite, Shubhangi P.; Bansode, Ajay H.; Burate, Pralhad A.; Suryayanshi, Gurunath (Asian Journal of Organic Chemistry, 2019)
An efficient AgNO3-catalysed method has been developed for the synthesis of functionalized cyclopentanones and spiro-cyclopentanones through intramolecular cyclization between ynones and cyanoacrylate/aryl/alkylidene malononitrile using DBU as a base. Easy availability of starting materials and mild reaction conditions makes this protocol more feasible over previously reported methods. The functionalized cyclopentanones and spiro-cyclopentanones were synthesized in good to excellent yields with a broad substrate scope.

Amino acid amide based ionic liquid as an efficient organo-catalyst for solvent-free knoevenagel condensation at room temperature - Burate, Pralhad A.; Javle, Balasaheb R.; Desale, Pranjal H.; Kinage, Anil K. (Catalysis Letters, 2019)
Ionic liquids of amino acid amide were synthesized and used as an efficient catalyst for solvent-free Knoevenagel condensation. Synthesized ionic liquids are an environmentally benign, inexpensive, metal free and plays the dual role of solvent as well as an efficient catalyst for Knoevenagel condensation. A wide range of aliphatic, aromatic and heteroaromatic aldehydes easily undergo condensation with malononitrile and ethyl cyanoacetate. The reaction proceeds at room temperature without using any organic solvent and is very fast with good to excellent yield. Additionally, the catalyst is easily separable and recyclable without loss of activity. [GRAPHICS] .
Keywords: Acrylonitrile; Amino acid amide; Cyanoacrylate; Ionic liquid; Knoevenagel condensation; Solvent-free